Dual carrier-cargo hydrophobization and charge ratio optimization improve the systemic circulation and safety of zwitterionic nano-polyplexes. (February 2019) - Jackson, Meredith A.; Bedingfield, Sean K.; Yu, Fang; Stokan, Mitchell E.; Miles, Rachel E.; Curvino, Elizabeth J.; Hoogenboezem, Ella N.; Bonami, Rachel H.; Patel, Shrusti S.; Kendall, Peggy L.; Giorgio, Todd D.; Duvall, Craig L.
Abstract: While polymeric nano-formulations for RNAi therapeutics hold great promise for molecularly-targeted, personalized medicine, they possess significant systemic delivery challenges including rapid clearance from circulation and the potential for carrier-associated toxicity due to cationic polymer or lipid components. Herein, we evaluated the in vivo pharmacokinetic and safety impact of often-overlooked formulation parameters, including the ratio of carrier polymer to cargo siRNA and hydrophobic siRNA modification in combination with hydrophobic polymer components (dual hydrophobization). For these studies, we used nano-polyplexes (NPs) with well-shielded, zwitterionic coronas, resulting in various NP formulations of equivalent hydrodynamic size and neutral surface charge regardless of charge ratio. Doubling nano-polyplex charge ratio from 10 to 20 increased circulation half-life five-fold and pharmacokinetic area under the curve four-fold, but was also associated with increased liver enzymes, a marker of hepatic damage. Dual hydrophobization achieved by formulating NPs with palmitic acid-modified siRNA (siPA-NPs) both reduced the amount of carrier polymer required to achieve optimal pharmacokinetic profiles and abrogated liver toxicities. We also show that optimized zwitterionic siPA-NPs are well-tolerated upon long-term, repeated administration in mice and exhibit greater than two-fold increased uptake in orthotopic MDA-MB-231 xenografts compared to commercial transfection reagent, in vivo- jetPEI ® . These data suggest that charge ratio optimization has important in vivo implications and that dual hydrophobization strategies can be used to maximize both NP circulation time and safety. Graphical abstract: Image 1